Obrashchenie Prezidenta RF B.N. El'tsina k grazhdanam Rossii . Obrashchenie Prezidenta RF B.N. El'tsina k grazhdanam Rossii . Message from the President of Russian Federation Boris Yeltsin to the Russian Citizens . Обращение Президента РФ Б.Н. Ельцина к гражданам России - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The President's speech about political confrontation and crisis of statehood in Russia. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation) Речь президента о политическом противоборстве и кризисе государственности в России. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации)